Borderlands Saints : Secular Sanctity in Chicano/a and Mexican Culture - Martín, Desirée A., 1972- (Latinidad: Transnational Cultures in the United States., 2014)
Borderlands Saints examines the rise and fall of popular saints and saint-like figures in the borderlands of the United States and Mexico. Focusing specifically on Teresa Urrea (La Santa de Cabora), Pancho Villa, César Chávez, Subcomandante Marcos, and Santa Muerte, the book traces the intersections of these figures, their devotees, artistic representations, and dominant institutions with an eye for the ways in which such unofficial saints mirror traditional spiritual practices and serve specific cultural needs.